10 - Researching the Public Good: Reflections on Experiences of Doing Research on Higher Education and he Public Good in South Africa - Ngcwangu, Siphelo (Journal of Higher Education in Africa, 2022)
This article discusses the experience of doing research on higher education and the public good in South Africa within a bigger project titled ‘Higher Education, Inequalities and the Public Good: Perspectives from Four African Countries’. Qualitative data was collected through key informant interviews by a team of eight researchers who concentrated on specific groups of stakeholders as per the themes of the research. The aim of the interviews was to understand the perceptions of stakeholders both within and outside the university system on the public good role of university education in South Africa. This article focuses on three key issues: locating the research in the context of South Africa’s democratic transition, methodological challenges and pitfalls, tensions, and missing questions/silences. We were doing our research in the aftermath of the student protests of 2015 and 2016, and many of the stakeholders we interviewed were actively involved in making sense of the issues that the students raised. The research team formulated the ‘DNA’ framework for analysing qualitative data from the stakeholders, which refers to the descriptive, normative and analytic aspects of the data that pointed to a unique way in which we could frame our findings. By reflecting on the research process and our positionality in it, the paper contributes to the general field of qualitative research studies, bringing in the dynamics of conducting research in large-scale cross-national projects.